Multistate Outbreak of Human Salmonella Typhimurium Infections Linked to Pet Hedgehogs – United States, 2011–2013. (13th October 2016) - Anderson, T. C.; Marsden‐Haug, N.; Morris, J. F.; Culpepper, W.; Bessette, N.; Adams, J. K.; Bidol, S.; Meyer, S.; Schmitz, J.; Erdman, M. M.; Gomez, T. M.; Barton Behravesh, C.
Summary: Zoonotic Salmonella infections cause approximately 130 000 illnesses annually in the United States. Of 72.9 million US households owning at least one pet, five million own small mammals; 3000 hedgehogs were documented by USDA in USDA‐licensed breeding facilities and pet stores in 2012. State health department collaborators and PulseNet, the national bacterial subtyping network, identified human infections of a Salmonella Typhimurium outbreak strain, which were investigated by CDC, USDA‐APHIS and state public and animal health officials. A case was defined as an illness in a person infected with the outbreak strain identified between 1 December 2011 and 3 June 2013. Investigators collected information on patient exposures, cultured animal and environmental specimens for Salmonella, and conducted traceback investigations of USDA‐licensed hedgehog facilities. There were 26 cases in 12 states. Illness onset dates ranged from 26 December 2011 to 8 April 2013. The median patient age was 15 years (range = <1–91 years); 58% were female. Among 23 persons with available information, 8 (35%) were hospitalized and one outbreak strain ‐ associated death was reported. Of 25 patients with available information, 20 (80%) reported pet hedgehog contact in the week before illness onset. The outbreak strain was isolated from animal and environmental samples collected from three ill persons' homes in three states. Hedgehogs were purchased in geographically distant states from USDA‐licensed breeders (10/17, 59%); a USDA‐licensed pet store (1/17,  6%); unlicensed or unknown status breeders (3/17, 18%); and private individuals (3/17, 18%). Traceback investigations of USDA‐licensed facilities did not reveal a single source of infection. Public and animal health collaboration linked pet hedgehog contact to human infections of Salmonella Typhimurium, highlighting the importance of a One Health investigative approach to zoonotic salmonellosis outbreaks. More efforts are needed to increase awareness among multiple stakeholders on the risk of illness associated with pet hedgehogs.